Unique magnetic and thermoelectric properties of chemically functionalized narrow carbon polymers. (24th November 2016) - Zberecki, K; Wierzbicki, M; Swirkowicz, R; Barnaś, J
Abstract: We analyze magnetic, transport and thermoelectric properties of narrow carbon polymers, which are chemically functionalized with nitroxide groups. Numerical calculations of the electronic band structure and the corresponding transmission function are based on density functional theory. Transport and thermoelectric parameters are calculated in the linear response regime, with particular interest in charge and spin thermopowers (charge and spin Seebeck effects). Such nanoribbons are shown to have thermoelectric properties described by large thermoelectric efficiency, which makes these materials promising from the application point of view.